2015
DOI: 10.1016/j.jspd.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Power-Assisted Pedicle Tract Preparation and Screw Placement

Abstract: The use of power tools to create pedicle tracts and place pedicle screws was associated with shorter fluoroscopy times and a lower revision rate compared with using manual tools. Both techniques posed similar low risks of injury to the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
1
21
0
2
Order By: Relevance
“…Despite that, preclinical studies showed comparable [ 15 17 ] fixation strength between the two. Conversely, a clinical study by Seehausen et al [ 18 ] showed a significantly lower failure rate for power-assisted placed screws. One possible explanation for that is the reduction in the wobble phenomenon, which may improve the bone-screw interface, but this point requires further investigation, hopefully from both clinical and preclinical studies.…”
Section: Pull-out Strengthmentioning
confidence: 98%
See 3 more Smart Citations
“…Despite that, preclinical studies showed comparable [ 15 17 ] fixation strength between the two. Conversely, a clinical study by Seehausen et al [ 18 ] showed a significantly lower failure rate for power-assisted placed screws. One possible explanation for that is the reduction in the wobble phenomenon, which may improve the bone-screw interface, but this point requires further investigation, hopefully from both clinical and preclinical studies.…”
Section: Pull-out Strengthmentioning
confidence: 98%
“…Considering the wide spread of pedicle screws and of the use of power tools in other districts, it is surprising that the first retrospective study about this topic has been written by Seehausen et al [ 18 ] only in 2015. They used a 2 mm drill bit to create the tract, and then they expanded it with a 3.22 mm bit; they then inserted the screw without any prior tap.…”
Section: Pull-out Strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Seehausen et al suggested that the use of power tools to place pedicle screws can provide shorter fluoroscopy times and lower revision rates than the use of manual tools and that both techniques had similar low risks of injury to patients 13) . We have used power tools in many cases involving open surgeries or minimally invasive spine stabilization (MISt) procedures.…”
Section: Introductionmentioning
confidence: 99%